Removal of Nitrate Nitrogen in Groundwater by Attapulgite Loaded with Nano-Zero-Valent Iron - Yangyang Zhang; Yunfeng Tan; Bo Zu; Xiaotian Zhang; Chunli Zheng; Zishen Lin; Fei He; Kejun Chen (Adsorption Science & Technology)
Nano-zero-valent iron (nZVI) can be used to remove nitrate nitrogen (NO3-N) from groundwater. However, it has low reduction efficiency owing to its oxidation and aggregation characteristics. Thus, nZVI-loaded material is used to alleviate these drawbacks. In this study, nZVI-coated attapulgite (ATP) was prepared for the removal of NO3-N from groundwater. ATP-nZVI was prepared using the chemical liquid deposition-coreduction method. The prepared materials were characterized by SEM, XRD, and XPS analyses, which confirmed that the aluminum silicate particles in the ATP structure are effective carriers of nZVI and effectively inhibit self-consumption caused by the oxidation and aggregation of nZVI. The batch experiments examined experimental samples containing 30 mg/L nitrate and analyzed the effects of various parameters, including the material, mass ratio, initial pH, initial temperature, and coexisting anions on the NO3-N removal efficiency. The results showed that the optimal removal rate of the composite was 78.61%, which is higher than that using the same amount of ATP, iron powder, and nZVI. When the mass ratio of ATP to nZVI was 1 : 1, the NO3-N removal efficiency was the highest. When the pH value increased from 3 to 9, the NO3-N removal rate decreased, while an increase in the reaction temperature promoted NO3-N removal. The order of the inhibitory effect of coexisting anions on NO3-N removal by various nanoions was PO43–>CO32–>SO42–>Cl–. The adsorption kinetic model fitting results indicated that the chemisorption of electron exchange between ATP and nZVI in NO3-N removal was the main rate-limiting step in the reaction. This study demonstrates the potential of the prepared ATP-nZVI composite for NO3-N removal from groundwater.